2016
DOI: 10.1212/wnl.0000000000002720
|View full text |Cite
|
Sign up to set email alerts
|

A dual concurrent mechanism explains trigeminal neuralgia in patients with multiple sclerosis

Abstract: Our observation that in many patients with MS-related TN a pontine demyelinating plaque and neurovascular compression coexist should prompt neurologists to seek possible neurovascular compression in patients with MS-related TN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 32 publications
4
86
2
3
Order By: Relevance
“…It may be that both this specific transmembrane mutation and vascular compression must be present to develop HFS/TN in this family. A similar “double crush” mechanism has been proposed for multiple sclerosis associated TN, where most cases demonstrate both a pontine lesion and vascular compression of the trigeminal nerve …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It may be that both this specific transmembrane mutation and vascular compression must be present to develop HFS/TN in this family. A similar “double crush” mechanism has been proposed for multiple sclerosis associated TN, where most cases demonstrate both a pontine lesion and vascular compression of the trigeminal nerve …”
Section: Discussionmentioning
confidence: 72%
“…A similar "double crush" mechanism has been proposed for multiple sclerosis associated TN, where most cases demonstrate both a pontine lesion and vascular compression of the trigeminal nerve. 44 Supporting this theory is the family member (VI-20) with HFS but without the G163R mutation. Her HFS was apparently due to adjacent tortuous vessels, indicating that the MPZ mutation alone is not sufficient to cause HFS/TN but is acting as a strong risk factor for the trait.…”
Section: Discussionmentioning
confidence: 90%
“…Papers studying the diagnostic accuracy of clinical characteristics for distinguishing primary from secondary TN were sought. In addition to the papers included in the previous guideline [6][7][8][9][10][11], two new papers were identified [12,13]. Involvement of the first trigeminal division and poor response to treatment were not significantly associated with secondary TN (Table 1).…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
“…Interestingly, a recent imaging study found an association between TN and MS lesions not only in the pontine tri- geminal afferents but also in the contralateral insular region and hippocampus [21]. Finally, in some patients with MS-related TN, a demyelinating plaque and neurovascular compression coexist [22]. The treatment of TN differs from that of other neuropathic pain syndromes.…”
Section: Neuralgiasmentioning
confidence: 99%